Comparison of the Ability of High and Low Virulence Strains of Non-cytopathic Bovine Viral Diarrhea Virus-1 to Modulate Expression of Interferon Tau Stimulated Genes in Bovine Endometrium - Wang, Kai; Thomas, Carole; Zhang, Shujun; Wathes, D. Claire; Cheng, Zhangrui (Frontiers in Veterinary Science, 2021)
Bovine Viral Diarrhea virus (BVDV) is a pestivirus with a single-stranded, positive sense RNA genome. It is endemic in many cattle populations, causing major economic losses in part due to reduced fertility. BVDV exhibits great genetic diversity and is classified as type 1 or 2 (BVDV-1, BVDV-2) with either non-cytopathogenic (ncp) or cytopathogenic (cp) biotypes. Differing strains of ncpBVDV differ in virulence, affecting clinical outcome. BVDV replicates in the reproductive tract, affecting host immunity and embryo survival. This study used an in vitro model of primary bovine endometrial cell cultures to compare the effects of two BVDV ncp type 1a strains of differing virulence (termed HO and KY) on endometrial transcription of candidate interferon stimulated genes (ISG) using qPCR. Half the cultures were stimulated with interferon tau (IFNT, the conceptus produced pregnancy recognition factor) in the presence or absence of viral infection. Cultures were replicated on cells from 10 BVDV-free cows. IFNT treatment stimulated transcription of 10 candidate ISGs, whereas both ncpBVDV-1 strains alone inhibited transcription of 8/10 ISGs. In combined BVDV-1+IFNT cultures, the stimulatory effect of IFNT on expression of GBP4, ISG15, HERC5, RSAD2, IFIH1, IFIT3, and MX1 was significantly inhibited by HO, but only ISG15, RSAD2, IFI27, and IFIT3 were decreased by KY. Inhibition by HO was generally greater. The IFNT-induced expression of TRIM56 was, however, increased by HO. These data show that HO, the more virulent ncpBVDV-1 strain, has a greater capacity to inhibit key antiviral pathways. These differences need confirmation at the protein level but may influence immune tolerance of the host. They could also reduce fertility by increasing uterine susceptibility to bacterial infection and disrupting IFNT-mediated pregnancy recognition.